Design and Validation of an Acceptance and Commitment Therapy-Based Intervention Package for Mothers of Children with Intellectual Disabilities - Moradi, Sajede; Samani, Siamak; Mozafari, Mohammad; Omidvar, Banafsheh (Psychology of Woman Journal, 2024)
Objective: The present study was conducted with the main objective of explaining the content validity of the ACT-based intervention package for mothers of children with intellectual disabilities, which was designed by the researcher. Methods and Materials: This research is exploratory in terms of its objective and is classified as qualitative in nature. The study population consisted of all books, articles, and dissertations in Persian and English regarding ACT-based therapeutic programs for mothers of children with intellectual disabilities, considering the research’s dependent variables over the last 20 years. Additionally, the population included all experts in the psychology department of Islamic Azad University, Shiraz Branch, who are specialists in the field of intellectual disabilities. The sample from the study population, which included books, articles, and dissertations, was selected using purposeful sampling, and the sampling continued until theoretical saturation was reached. Additionally, from the psychology department of Islamic Azad University, Shiraz Branch, eight psychology professors (experts in the field of special education) were selected. A researcher-made content validity evaluation questionnaire was used to collect experts’ opinions regarding the content validity of the ACT-based intervention program. Findings: The findings showed that the ACT-based intervention package had an acceptable level of content validity, with the CVR (Content Validity Ratio) of all sessions in the intervention program ranging between 0.75 and 1, indicating appropriate content validity for this program. Conclusion: It is recommended that therapists and counselors in the field of therapy use this approach at both educational and therapeutic levels to improve self-compassion, hope, and acceptance in mothers of children with intellectual disabilities.